Franciszek Majchrowicz (1858–1928) – pedagog i historyk wychowania. Kilka uzupełnień do biografii - Wałęga, Agnieszka (Biuletyn Historii Wychowania, 2009)
Franciszek Majchrowicz was a renowned Lvov-based educator and a historian of education. Throughout many years of his professional career he was involved in teaching in secondary schools and teachers’ training colleges. At the same time, he was actively participating in educational initiatives as an activist. Majchrowicz was a co-editor of the periodical Rodzina i Szkoła [Family and School], co-operated with the Council of National Education in Galicia (Eastern Poland) and with the School Board of the Lvov province. His publishing output included numerous articles and pedagogical texts as well as historical and educational works, including one of the first textbooks for teaching history of education in teachers’ training colleges (with many editions throughout the years 1901-1924). Majchrowicz also published source materials for the history of Polish education, promoted the educational ideas of the Commission of National Education and attempted to develop the history of education into a coherent academic discipline for researchers and a subject in the national curriculum for educators. The hitherto available historical and educational literature lacks comprehensive and detailed information on his university education or professional training and qualifications. The present work attempts by no means to be exhaustive or to offer a comprehensive coverage of a full biography of Franciszek Majchrowicz as an educator and historian of education. It merely complements some facts and explanations that have already been published earlier, and provides some new information that may help resolve doubts concerning certain aspects of his professional career presented in the hitherto published body of works on the subject. It is mostly due to the archival material from Lvov (this mainly comprises students catalogues and minute books of doctoral examinations from the National District Archive), constituting the source base for the present work, that providing complete answers to such issues as the course of Majchrowicz’s studies, his doctoral dissertation procedure and the scope of his teacher’s examination, have become possible. The above source material made it also possible to conclude with certain remarks regarding the masters Majchrowicz had in great esteem and their influence upon research and academic interests of the Lvov-based educator and historian of education.